Aerosol transmission of SARS‐CoV‐2 by children and adults during the COVID‐19 pandemic - Moschovis, Peter P. (Pediatr Pulmonol, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) can be transmitted via respiratory droplets, aerosols, and to a lesser extent, fomites. Defining the factors driving infectivity and transmission is critical for infection control and containment of this pandemic. We outline the major methods of transmission of SARS‐CoV‐2, focusing on aerosol transmission. We review principles of aerosol science and discuss their implications for mitigating the spread of SARS‐CoV‐2 among children and adults.